Determinants of Information and Communication Technology Sector Development in Java Island, 2016-2020 - Ira Helsa Triana; Siskarossa Ika Oktora (EKO-REGIONAL, 2022)
The Information and Communication Technology (ICT) sector is one of the main drivers of economic growth, so the condition of the ICT sector becomes an essential factor in development. The ICT sector consists of the manufacturing and service sectors whose main activities are related to the development, production, commercial and intensive use of ICT. In 2016-2020, six provinces on Java Island became the provinces with the highest IP-ICT scores. Java Island had a GDP share of 59 percent of Indonesia's GDP in 2020. Meanwhile, the ICT sector's GDP share of Indonesia's total GDP was 4.25 percent in 2020. This study aims to analyze factors that affect the development of the ICT sector in Java Island , 2016-2020. The data used is secondary data from Statistics Indonesia. Using the panel data regression, the results show that the number of workers in the ICT sector, the average length of schooling, and internet users had a significant and positive effect on the development of the ICT sector in Java Island in 2016-2020. The level of household consumption for telecommunications has no significant impact on ICT sector development in Java in 2016-2020.